Metallic glass-based chiral nanolattice: Light weight, auxeticity, and superior mechanical properties. Issue 10 (December 2017) - Sha, Z.D.; She, C.M.; Xu, G.K.; Pei, Q.X.; Liu, Z.S.; Wang, T.J.; Gao, H.J.
Graphical abstract: Abstract: Metallic glasses (MGs) possess large elastic limit and high strength, but unfortunately they are of limited commercial utility due to their macroscopic brittle nature. Here, we report that a chiral nanolattice can be used to design large-scale MGs with negative Poisson's ratio, large elastic deformation capability, extensive hardening, and large ductility. Furthermore, the mechanical behaviors of the metallic glass chiral nanolattice (MGCN) can be significantly altered through changing the thickness and length of the ligaments in the nanolattice. An exceptional combination of high strength and ductility is observed for MGCN with thin and long ligaments, wherein the sample density is only twice that of water. The deformation mechanism that characterizes the chiral topology is a combination of rotation of the nodes with bending and extension of the ligaments, leading to the extraordinary mechanical behaviors. The present study not only offers a potential solution to mitigating the brittleness of MGs, but also provides some guidelines in designing large-scale MG meta-materials for prospective applications in the fields of acoustics and energy absorption.